WHAT MATTERS IN SELECTING A CAFÉ? A CASE OF MILLENNIALS - Egi Arvian Firmansyah; Fitria Atni Nurjannah; Deru R Indika; Ardi Gunardi (Jurnal Manajemen dan Pemasaran Jasa, 2019)
This paper aims to portray the criteria considered important by Millennials in selecting a café and investigate the gender preference regarding those criteria. The questionnaires were distributed to 100 café visitors. The research results using Rasch analysis showed that ‘comfort’ is generally the most important criterion of a café. Nonetheless, male and female Millennials do not always have a consensus where male Millennials prefer ‘innovativeness’ to other criteria while female Millennials prefer ‘comfort, varied menus, and unique menus’ to others. Other criteria aside from these four criteria are not significantly different among the two groups of gender. This paper gives implication for the culinary businesses in setting strategies targeting the Millennials who are presently the largest population group in Indonesia. This research also benefits any party interested in studying the characteristics and selection criteria of the Indonesian Millennials.